Ultraweak luminescence of the Characeae plants under the circumstances of cyclical changes in temperature - Borc, Robert; Dudziak, Andrzej; Jaśkowska, Anna (Current Topics in Biophysics, 2012)
The study sought to measure ultraweak chemiluminescence (UWL) of Nitellopsis Obtusa plants with regards to temperature changes within the range from 4°C to 38°C. The temperature changes were being executed in reversible cycles. The variations of UWL intensity with temperature had an exponential character. In case when temperature was changed rapidly by 5°C every 20 min or fluently with rate of 0.17 °C/min we observed a temperature hysteresis loop in the first cycles and the loop character disappeared in the second cycles. When the temperature was being changed fluently but faster (1.3 °C/min) after 3 cycles (about 2 hours) the curves no longer manifested the loop character. This phenomenon can point that the plants adapted themselves to the temperature changes. We also observed a stimulation of UWL made in successful cycles. Our spectral experiments showed that the UWL may consist mainly of emission of the singlet oxygen sigma (762 nm) and induced emission of chlorophyll.